Gender-based approaches for improving milk safety, value addition, and marketing among smallholder livestock farmers - Nagasha, Judith Irene; Ocaido, Michael; Rajala, Elisabeth; Abu Hatab, Assem; Chiwona-Karltun, Linley (Frontiers in Sustainable Food Systems, 2024)
In the context of Uganda, this study delves into gender-based strategies aimed at enhancing women's engagement in milk safety, value addition and marketing within smallholder livestock farming. The objectives were twofold: first, to document the current practices of women in milk safety, value addition, and marketing channels; second, to examine the constraints, opportunities, and strategies related to the production of safe milk and milk products, along with accessing sustainable markets. Conducted in four sub-counties of Kiruhura district, this research employed both qualitative participatory methods and structured questionnaires, including twelve focused group discussions and twenty key informant interviews with both women and men. Notably, 217 structured questionnaires were administered. The findings illuminate that women play a central role in milk processing, water provisioning, sanitation, hygiene practices and were the primary contributors to milk value addition, particularly in the production of butter and ghee. Despite their active involvement, women face challenges in accessing adequate milk quantities, employ traditional labor-intensive procedures and encounter difficulties in marketing their processed products. Men, often the household heads, held decision-making authority over milk consumption and control the selling of milk, contributing to gender disparities. Addressing these challenges necessitates comprehensive support, including training and capacity-building initiatives for both men and women in milk value addition, credit access, and market entry. The study underscores the potential for improved women's access to milk quantities, particularly for butter and ghee production, to strengthen rural livelihoods and boost dairy production in Uganda.